A New Era of Nuclear Criticality Experiments: The First 10 Years of Radiation Test Object Operations at NCERC. (5th November 2021) - Hutchinson, Jesson; Bounds, John; Cutler, Theresa; Dinwiddie, Derek; Goda, Joetta; Grove, Travis; Hayes, David; McKenzie, George; McSpaden, Alexander; Miller, James; Myers, William; Ordonez Ferrer, Ernesto Andres; et al.
Abstract: The work presented in this paper focuses on the first 10 years (2011–2020) of radiation test object (RTO) operations at the National Criticality Experiments Research Center. RTOs are subcritical configurations of special nuclear material that are built by hand. These configurations are utilized for benchmark experiments, detector testing/characterization, and training. An overview of the types of measurements used in RTO operations is given as well as a history of RTO operations at Los Alamos National Laboratory from 1944–2011.